Analysis and Testing of Chain Characteristics and Rheological Properties for Magnetorheological Fluid. (24th November 2013) - Chen, Song; Huang, Jin; Shu, Hongyu; Sun, Tiger; Jian, Kailin
Abstract : Digital holographic microscopy is presented in this study, which can measure the magnetorheological (MR) fluid in different volume fractions of particles and different magnetic field strengths. Based on the chain structure of magnetic particle under applied magnetic field, the relationships between shear yield stress, magnetic field, size, and volume fraction of MR fluid in two parallel discs are established. In this experiment, we choose three MR fluid samples to check the rheological properties of MR fluid and to obtain the material parameters with the test equipment of MR fluid; the conclusion is effective.